2008
DOI: 10.1002/jctb.2082
|View full text |Cite
|
Sign up to set email alerts
|

Production of fuel ethanol from softwood by simultaneous saccharification and fermentation at high dry matter content

Abstract: BACKGROUND: The production of bio-ethanol from softwood is considered a promising alternative to fossil fuels in Sweden. In order to make fuel ethanol economically competitive with fossil fuels, it is important to reduce the production cost, which can be done by increasing the dry matter content of the fermentation medium, thus reducing the energy demand in the final distillation of the fermentation broth. Running simultaneous saccharification and fermentation (SSF) at higher dry matter content has, however, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 36 publications
4
62
0
Order By: Relevance
“…These findings were in agreement with Romaní et al (2014) and Hoyer et al (2009), who reported better performance for SSF than PSSF. The PSSF process significantly increased the % cellulose conversion only when the % cellulose conversion and ethanol concentration were low in the SSF process, but otherwise, it did not have a significant effect, or even had a negative effect when a high cellulose conversion and ethanol content were obtained without a pre-hydrolysis step (Hoyer et al 2013).…”
Section: Pssf Vs Ssfsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings were in agreement with Romaní et al (2014) and Hoyer et al (2009), who reported better performance for SSF than PSSF. The PSSF process significantly increased the % cellulose conversion only when the % cellulose conversion and ethanol concentration were low in the SSF process, but otherwise, it did not have a significant effect, or even had a negative effect when a high cellulose conversion and ethanol content were obtained without a pre-hydrolysis step (Hoyer et al 2013).…”
Section: Pssf Vs Ssfsupporting
confidence: 92%
“…Moreover, according to Hoyer et al (2009) andLópez-Linares et al (2014a), the use of higher pretreated biomass loadings (up to 10%) resulted in a higher ethanol concentration and, at same time, no significant decrease in the cellulose conversion occurred. These results confirmed that there was no end-product accumulation during the SSF process when using a less than 10% biomass concentration, which was the limit to obtain good cellulose conversion (Olofsson et al 2008).…”
Section: Simultaneous Saccharification and Fermentation (Ssf)mentioning
confidence: 98%
See 1 more Smart Citation
“…24,25 Very recently, interesting results were discussed on SSF in a fluidized bed reactor (MSFBR) using glucose. Molasses gave comparative ethanol productivity in comparison to glucose in the MSFBR.…”
Section: Introductionmentioning
confidence: 99%
“…Manzanares et al [29] also found that with increasing initial DM content, a separate saccharification step improves fermentation of liquid hot waterpretreated olive-pruning biomass. Finally, Hoyer et al [30] reported that with increasing DM content, even 4 h of saccharification could significantly improve fermentation of softwoods.…”
Section: Resultsmentioning
confidence: 99%